El Serapeo o Serapeum: Templo, Biblioteca y Centro de Investigaciones Científicas - Fernández Abad, Francisco Javier (Revista General de Información y Documentación, 2009)
The Museum of Alexandria was possessing the second library where it was depositing the remaining funds of the principal library. It was located in Serapis’s temple, founded by Ptolemy the IIIrd and was named as Serapeo. It used as bridge among the Egyptian culture and the Greek culture, and turned into center of scientific investigations after the destruction of the Museum. It was closed and destroyed after the edicts of the emperor Teodosio I against the pagan culture in 391 A.D.